Application of CRISPR Technology in the Environment - AL-mamoori, Ayad M.J.AL-mamoori (Sulaimani Journal for Humanities, 2025)
CRISPR technology is a novel platform for genome editing that enables robust, effective, and flexible alterations to the genome sequence in diverse organisms. The application of CRISPR in environmental biotechnology is developing rapidly, providing feasible and innovative solutions to urgent environmental issues related to pollution remediation, responsible food production, biodiversity conservation, and mitigating and adapting to climate change. For example, CRISPR-mediated knockouts of starch biosynthesis genes in Chlamydomonas reinhardtii have doubled triacylglycerol content, boosting biodiesel yield, and CRISPR modification of rice root oxygen release genes reduced methane emissions by about 30% without affecting yield. Developing ways to utilise CRISPR has applications in manipulating microorganisms for bioremediation, such as Shewanella oneidensis strains engineered with CRISPR-ddAsCpf1 that degraded toxic phenolic compounds 60% faster than controls, enhancing algae production of biofuels with greater efficiency, creating biosensors for environmental monitoring with femtomolar detection limits, and methods to grow plants and livestock that mitigate greenhouse gas emissions. CRISPR-based approaches are also being genetically engineered to help manage invasive species, increase the water and nutrient use efficiency of crops, prolong the shelf life of food and mitigate food waste, such as non-browning mushrooms with polyphenol oxidase gene knockouts that show extended shelf life. However, despite its potential, CRISPR technology remains hindered by technical limitations and ecological risks, as well as philosophical and ethical concerns regarding its application on a larger scale. Integrating CRISPR with alternative technologies, establishing effective biosafety regulations, and adopting an ecological approach for its applications and efficacy, while conducting risk–benefit analyses, will be necessary for utilizing CRISPR responsibly across environmental systems in a sustainable manner.
Keywords: CRISPR; genetic engineering; bioremediation; environmental conservation; invasive species; sustainable agriculture; ecological safety; gene editing